Pertanggungjawaban Pidana Pelaku Penyebar Berita Bohong (HOAX) di Media Sosial (Studi Penelitian di Pengadilan Negeri Lhokseumawe) - kausar, henry; Hatta, Muhammad; Hamdani, Hamdani (Fakultas Hukum Universitas Malikussaleh, 2023)
Hoax is information that is engineered to cover up real information, in other words hoax is defined as an attempt to distort facts using information that is convincing but cannot be verified. Covering information, Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) is the first law in the field of electronic transaction information technology as a product of legislation that is urgently needed and has become a pioneer laying the foundation for regulations in the field of utilization of information technology and transactions electronic. With the existence of laws and regulations that regulate information systems and electronic transactions, at least it can be a reference for law enforcement to take action on cases circulating on social media, such as now, for example regarding the spread of fake news or what is known as hoax news. Criminal liability is determined after a crime has been committed. In order to be held criminally responsible, a person must first be proven that he has fulfilled the elements of the crime he was charged with. This study aims to find out the form of criminal responsibility for the perpetrators of spreading fake news (hoax) on social media based on Law Number 19 of 2016 concerning Information and Electronic Transactions and how Criminal Responsibility is for the crime of spreading fake news (hoax) in the Judicial Area Lhokseumawe State, the type of research conducted is empirical normative research, namely field research where data is obtained from field interviews, observation and documentation which are processed qualitatively so as to obtain valid results.